Answer:
![Fx=(5\pm√(25+24) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/68e127xlyd999zsw9h6vak2s30u2fifaze.png)
Explanation:
A quadratic equation in one variable given by the general expression:
![ax^2+bx+c](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2l7bgpnc614y04iljycygusm3pon0vhiuh.png)
Where:
![a\\eq 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cmvbteb0x7royb1zj3ygws4tjelg9ig1dd.png)
The roots of this equation can be found using the quadratic formula, which is given by:
![x=(-b\pm√(b^2-4ac) )/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/slv1i3wrs0tu4oudgu3ojp323chawqq6ca.png)
So:
![y(x)=3x^2-5x-2=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/dc80zs9qxt9q9jt3ridsot9n4u674obf0i.png)
As you can see, in this case:
![a=3\\b=-5\\c=-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/1dwjup5mmaw3w8bwf7g37q9rmeug59ymel.png)
Using the quadratic formula:
![x=(-b\pm√(b^2-4ac) )/(2a)=(-(-5)\pm√((-5)^2-4(3)(-2)) )/(2(3))=(5\pm√(25+24) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/79qqq8idcpdcrv5qeg7e65xv9rho92sqrq.png)
Therefore, the answer is:
![Fx=(5\pm√(25+24) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/68e127xlyd999zsw9h6vak2s30u2fifaze.png)